(untitled) (Journal of the College of Basic Education, 2022)
The study aimed to identify teachers ’attitudes towards the use of e -learning by gender, and to achieve the goal of the study, the researcher constructed a scale consisting of (35) items, and the study sample reached (200) teachers who were chosen by the random stratified method. The validity of the tool was verified by apparent validity. By presenting it to the experts and confirming the construction and reliability of the Alpha Cronbach method, and the researcher used to analyze his results a number of statistical methods, including the Pearson correlation coefficient and the T-test for one sample and the T-test for two independent samples. There are no statistically significant differences between male and female teachers in their attitudes towards the use of e-learning, and the study came out with a number of recommendations and proposals.